AIR CONTROL AND CONTESTED SOVEREIGNTY: MALAYSIA’S SECURITY DILEMMA AMID CHINA'S PROSPECTIVE ADIZ IN THE SOUTH CHINA SEA - Haron, Zulkarnain; Taib, Khairul Nizam; Md Saman, Mazura (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
China’s potential declaration of an Air Defence Identification Zone (ADIZ) over the South China Sea (SCS) poses critical strategic and security challenges, particularly for Malaysia as a key littoral and claimant state in the disputed region. Drawing on its 2013 precedent in the East China Sea, Beijing could employ an ADIZ as a strategic instrument to consolidate control over contested airspace, reinforcing its expansive territorial claims under the “nine-dash line.” Such a move would not only heighten regional tensions but also directly affect Malaysia’s airspace sovereignty and strategic posture. The objective of this study is to examine the concept of ADIZs within the framework of international law, focusing on the legal ambiguities in existing mechanisms such as the United Nations Convention on the Law of the Sea (UNCLOS) and International Civil Aviation Organization (ICAO) guidelines. It also seeks to assess the security, diplomatic, and legal implications of a Chinese-declared ADIZ for Malaysia. Using a qualitative research methodology, the paper conducts a doctrinal legal analysis of ADIZ norms and precedents, complemented by a case study of China’s East China Sea ADIZ to identify operational and diplomatic patterns. The findings reveal three primary risks for Malaysia: militarily, the overstretching of the Royal Malaysian Air Force’s (RMAF) surveillance and interception capabilities; diplomatically, the strain on Malaysia’s balancing act between deep economic engagement with China and its defence commitments under frameworks like the Five Power Defence Arrangements (FPDA); and legally, the infringement of sovereignty should China enforce measures within Malaysia’s Exclusive Economic Zone (EEZ). The study concludes that Malaysia should adopt a multi-pronged strategy by enhancing regional air defence cooperation, leveraging ASEAN-led security mechanisms and pursuing confidence-building measures with China. A strategic hedging approach is vital to safeguard Malaysia’s air sovereignty and contribute to regional stability.